Primary Cervical Cancer Screening With Human Papillomavirus. Issue 5 (May 2015) - Wright, Thomas C.; Stoler, Mark H.; Behrens, Catherine M.; Sharma, Abha; Zhang, Guili; Wright, Teresa L.
<x xml:space="preserve">Abstract</x> ABSTRACT Human papillomavirus (HPV) testing has been used in the United States as a follow-up test for women with a cytology finding of atypical squamous cells of undetermined significance (ASC-US) and as an adjunct to cytology for women 30 years or older (cotesting). Numerous cross-sectional and randomized screening trials have demonstrated that HPV primary screening is more sensitive than cytology and can detect CIN3+ earlier. Several randomized trials, mainly in Europe, have reported that cotesting provides minimal increased protection against the subsequent development of cervical cancer than HPV primary screening. This article presents the 3-year end-of-study results of the first large, prospective screening study of HPV primary screening in the United States. The ATHENA (Addressing the Need for Advanced HPV Diagnostics) study evaluated the Cobas HPV Test as the primary screening test in women 25 years or older. The performance of HPV primary screening was compared with that of other screening strategies. A total of 42, 209 women 25 years or older were enrolled and had cytology and HPV testing. All women with abnormal cytology (≥ASC-US) and those who were HPV positive were referred to colposcopy. Women who did not have CIN2+ entered the 3-year follow-up phase; those diagnosed with CIN2+ during follow-up exited the study. The 3-year cumulative incidence rate of CIN3+ was 0.8% in cytology-negative women (95% confidence interval [CI], 0.5%–1.1%) and 0.3% in both HPV-negative women (95% CI, 0.1%–0.7%) and cytology and HPV-negative women (95% Cl, 0.1%–0.6%). The highest sensitivity for detection of CIN3+ over 3 years was found for HPV primary testing (76.1%; 95% CI, 70.3%–81.8%); sensitivity for detection of CIN3+ was 47.8% (95% CI, 41.6%–54.1%) for cytology and 61.7% (95% CI; 56.0%–67.5%) for the hybrid strategy (cytology if 25–29 years and cotesting with cytology and HPV if aged ≥30 years). In women 25 years or older, specificity for CIN3+ for cytology was 97.1% (95% CI, 96.9%–97.2%), and that for the hybrid strategy was 94.6% (95% CI, 94.4%–94.8%); specificity for CIN3+ for HPV primary was 93.5% (95% CI, 93.3%–93.8%). Although significantly more cases of CIN3+ were detected in women 25 years or older with HPV primary than with cytology or hybrid strategy, more colposcopies were required. However, the number of colposcopies per case of CIN3+ was the same as with the hybrid strategy. These findings demonstrate that HPV primary screening in women 25 years or older is as effective as a hybrid screening strategy using cytology for those 25 to 29 years old and cotesting if 30 years or older. Human papillomavirus primary screening requires less screening tests than cotesting. In women 25 to 29 years, cytology fails to detect about half the cases of CIN3+ identified with HPV primary. Moreover, a negative HPV test at baseline predicts one-half the risk of CIN3+ over 3 years compared with a negative cytology result.